Prognostic value of glucose to lymphocyte ratio for patients with renal cell carcinoma undergoing laparoscopic nephrectomy: A multi-institutional, propensity score matching cohort study - Ni, Jinliang; Li, Ziye; Song, Wei; Zhang, Houliang; Wang, Yidi; Zhang, Yifan; Zhang, Haipeng; Yang, Guangcan; Xie, Jun; Wang, Keyi; Peng, Bo; Mao, Weipu (Frontiers in Surgery, 2022)
Background We evaluated the prognostic value of preoperative blood glucose to lymphocyte ratio (GLR) in renal cell carcinoma (RCC) patients who underwent laparoscopic nephrectomy through a multi-institutional clinical study. Methods A total of 420 patients with RCC from three medical centers from 2014 to 2019 were included in this study. The effect of GLR on overall survival (OS) and cancer-specific survival (CSS) in RCC patients was assessed by Kaplan-Meier survival curves, univariate and multivariate Cox regression analysis. Moreover, a 1:1 propensity score matching (PSM) analysis of different GLR groups was utilized to further confirm the prognostic ability of GLR. Results The optimal cut-off value for GLR was 6.8. Patients were divided into high GLR and low GLR groups according to the optimal cut-off value. GLR was significant association with diabetes, cardiovascular disease and AJCC stage. High GLR predicted adverse OS (P = 0.002) and CSS (P < 0.01) in RCC patients. Multivariate Cox regression analysis revealed that high GLR was an independent prognostic factor for OS [hazard ratio (HR): 2.389, 95% confidence interval (CI), 1.136–5.027, P = 0.008] and CSS (HR: 3.474, 95% CI, 1.555–7.761, P = 0.002). After PSM analysis of the patients in the high GLR and low GLR groups, high GLR still predicted poor OS (P = 0.021) and CSS (P = 0.037). Conclusions High GLR is associated with adverse prognosis in RCC patients, and GLR can serve as an independent prognostic marker for OS and CSS in RCC patients receiving laparoscopic nephrectomy.